End of Life Care in Scotland: Trends in the Population in Need of Palliative Care - Schneider, Anna; Atherton, Iain (International Journal of Population Data Science, 2018)
Background Estimation of population-wide palliative care needs is crucial for end-of-life care planning, and literature around it has grown in the last years. However, no estimates have yet been published for Scotland. Objectives This paper provides estimates of how many people require palliative care in Scotland and describes changes in the composition of this subpopulation. What are their living arrangements? How have their medical conditions, health service use, and health trajectories changed? Methods (including data) The analysis is based on linked hospital records, death records, and Scottish Census data from 2001/02 and 2011/12. The palliative care estimation method by Murtagh et al. is utilised, as well as the illness trajectories distinguished by Murray et al. Comparative cross-sectional descriptive statistics are provided. Findings While a recent paper suggests that palliative care need in England/Wales has increased from 72.5% in 2006 to 74.9% in 2014, the share of people with a palliative care need among all deaths in Scotland has decreased from 80.6% to 78.3% in the period of this study. The share of people aged 85+ rose from 26.6% to 31.4%, and we observe a doubling of cases with prolonged dwindling at the end of their life. Despite their high need for care, 4 in 5 people lived in a private household in their last year of life, and 1 in 3 people lived alone. Conclusions Our findings suggest a change in the volume of care need and in the types of care required. They have strong implications for care providers.